Cell wall metabolism in Bacillus subtilis subsp. niger: accumulation of wall polymers in the supernatant of chemostat cultures. - de Boer, W (1981)
Cell wall polymers were measured both in the cells and in the cell-free medium of samples from steady-state chemostat cultures of Bacillus subtilis, growing at various rates under magnesium or phosphate limitation. The presence of both peptidoglycan and anionic wall polymers in the culture supernatant showed the occurrence of wall turnover in these cultures. Variable proportions of the total peptidoglycan present in the culture samples were found outside the cells in duplicate cultures, indicating that the rate of peptidoglycan turnover is variable in B. subtilis. Besides peptidoglycan, anionic wall polymers were detected in the culture supernatant: teichoic acid in magnesium-limited cultures and teichuronic acid in phosphate-limited cultures. In several samples, the ratio between the peptidoglycan and the anionic polymer concentrations was significantly lower in the extracellular fluid than in the walls. This divergency was attributed to the occurrence of direct secretion of anionic polymers after their synthesis.